Is dignity a useless concept? - Kalokairinou, Eleni (Ηθική. Περιοδικό φιλοσοφίας, 2021)
In this paper I undertake to examine Ruth Macklin’s claim that dignity is a useless concept. I explain her contention by the fact that dignity, as a concept, has a long history and has been presented differently at different times. I shed some light on certain different conceptions of dignity in ancient times and in our contemporary era. And I end up with the suggestion that the term “dignified”, like “good”, is a primarily evaluative term, unlike what some philosophers have thought.